2022
DOI: 10.3389/fcvm.2022.946027
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of atherectomy in treating severely calcified coronary lesions in patients with reduced left ventricular ejection fraction: A systematic review and meta-analysis

Abstract: BackgroundSeverely calcified coronary lesions with reduced left ventricular (LV) function result in worse outcomes. Atherectomy is used in treating such lesions when technically feasible. However, there is limited data examining the safety and efficacy of atherectomy without hemodynamic support in treating severely calcified coronary lesions in patients with reduced left ventricular ejection fraction (LVEF).ObjectiveTo evaluate the clinical outcomes of atherectomy in patient with reduced LVEF.MethodsWe searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…First, heavily calcified plaques impair the trabecular meshwork, disrupting drug-polymer from the stent surface and reducing the success rate and long-term effectiveness of PCI [ 7 ]. Second, the existence of calcified nodules impedes complete stent expansion and accurate apposition, leading to an increased rate of in-stent restenosis and stent thrombosis [ 8 ]. Despite being rare, stent thrombosis may cause myocardial infarction (MI) or cardiac death [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…First, heavily calcified plaques impair the trabecular meshwork, disrupting drug-polymer from the stent surface and reducing the success rate and long-term effectiveness of PCI [ 7 ]. Second, the existence of calcified nodules impedes complete stent expansion and accurate apposition, leading to an increased rate of in-stent restenosis and stent thrombosis [ 8 ]. Despite being rare, stent thrombosis may cause myocardial infarction (MI) or cardiac death [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under-expanded stents have been associated with poor long-term results (11). The outcomes of rotablation for coronary lesions could be affected by various clinical factors such as age, diabetes, renal insufficiency, LV function, and acute coronary syndrome (12)(13)(14)(15). In our previous studies, we have identified age, diabetes, renal insufficiency, ACS, cardiogenic shock, and residual Syntax score as prognostic factors for short and intermediate outcomes (16,17).…”
Section: Introductionmentioning
confidence: 99%